Job Satisfaction and Organizational Commitment as Factors Affecting Employee Withdrawal at Army Flight Center - Deden Komar Priatna; Annisa Fitri Anggraeni (Journal of Accounting and Finance Management, 2022)
The Army Aviation Center is the central implementing agency of the Indonesian Army, in carrying out its main tasks using aircraft requires a high level of security. One of the factors that support the creation of high security is by trying to overcome the problem of human resources, this is a serious concern by the leadership. The purpose of this study is to analyze the influence of organizational commitment and job satisfaction on employee withdrawals and the effect of the level of organizational commitment and job satisfaction together on the withdrawal of civil servants at the Army Aviation Center, either simultaneously or partially. The research method in this paper is quantitative, with a path analysis research model with a view to solving problems by collecting data, compiling data, then analyzing statistically and interpreting it to further obtain a valid result using the calculation of the Statistical Product And Service Solutions application. Based on the results of statistical data processing carried out, the research results obtained include organizational commitment has an influence on Employee Withdrawal and while job satisfaction on Employee Withdrawal is said to have an effect.